Frequency and Outcome of Cardiovascular Disease in Pregnant Women Presenting with Shortness of Breath in Low Resource Setup (Medical Forum Monthly, 2022)
Objective: To determine the frequency and causes of cardiac disease in pregnant women presenting to obstetric unit and to assess the associated maternal and fetal outcome in cardiac patients.Study Design: Descriptive Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Obetet and Gynae, Civil Hospital Karachi from June, 2020 to Dec, 2020 for a period of six months.Materials and Methods: Pregnant women between 18-40 years of any gestational age and parity presenting to antenatal clinic or emergency with complain of shortness of breath and/or palpitation were included in the study. Patients with hyperthyroidism and asthma were excluded .History pertinent to cardiovascular disease was taken followed by examination. Selected patients were seen by a consultant cardiologist and an echocardiography was performed. Patients diagnosed with cardiac disease were identified, treated in collaboration with cardiologist. Maternal and fetal outcome was noted. All data was analyzed for descriptive statistics.Results: A total of 252 pregnant women presenting with shortness of breath and/or palpitation were included in the study. Mean age of women was 31 years and mean gestational age was 35 years . Majority of patients were un booked( 77.8% n=14) and multipara (50%n=9) A total of 18 (7%)women were diagnosed as cardiac disease in pregnancy. The most common cause was valvular heart disease observed in 61.1 %(n=11) followed by cardiomyopathy in 27.7% (n=5) Congenital heart disease and ischaemic heart disease were diagnosed in 5.6% each (n=1). Mitral stenosis and regurgitation were common valvular lesions. ICU admission and ventilator support was required in 77.8% (n=14) and 55.6% (n=10) women respectively. Mortality rate was 11.1%(n=2) .Adverse fetal outcome included IUD in 22.2%(n=4) ,low birth weight16.7%(n=3),preterm birth 44.4%(n=8) and NND 5.6%(n=1).Conclusion: Cardiac disease in pregnancy is associated with significant maternal and perinatal morbidity and mortality